Metabolic and Inflammatory Signatures of Neurotrauma: Correlating Early Glycemic and Leukocytic Shifts with Glasgow Coma Scale Scores - Ni Wayan Lisa Suasti; Roland Sidabutar; Agung Budi Sutiono; Guata Naibaho (HM Publisher, 2026)
Background: Traumatic brain injury (TBI) precipitates a profound systemic physiological stress response, often termed the sympathetic storm, characterized by neuroendocrine dysregulation and widespread inflammation. While admission biomarkers such as White Blood Cell (WBC) count and Blood Glucose levels are routinely measured, their comparative utility in stratifying injury severity—particularly in distinguishing between moderate and severe phenotypes—remains under-characterized. This study aimed to evaluate the discriminatory power of these markers, hypothesizing that metabolic and immune responses exhibit distinct saturation kinetics relative to the Glasgow Coma Scale (GCS). Methods: We conducted a retrospective analytical observational study at Dr. Hasan Sadikin General Hospital (RSHS), a level I trauma center in Bandung, Indonesia. From an annual pool of admitted neurotrauma patients (January–December 2021), a stratified sample of 238 patients aged 18-60 years was analyzed. Strict exclusion criteria were applied to minimize confounders, including a history of metabolic disease and alcohol intoxication. TBI severity was stratified into mild (GCS 13-15), moderate (GCS 9-12), and severe (GCS 3-8). Statistical analysis utilized the Kruskal-Wallis and Mann-Whitney tests to assess non-parametric relationships. Results: The cohort was predominantly male (82.8%) and young (18-40 years, 68.9%). Both biomarkers correlated with overall severity; however, their trajectories diverged significantly. WBC counts exhibited a threshold effect, rising significantly from Mild (17.50 ± 6.56 x10³/µL) to Moderate (18.81 ± 5.27 x10³/µL) severity, but plateauing between moderate and severe groups (p>0.05), suggesting a saturation of the demargination response. Conversely, blood glucose displayed a graded linear escalation: Mild (133.11 ± 34.53 mg/dL), moderate (158.35 ± 49.59 mg/dL), and severe (226.14 ± 105.61 mg/dL) (p<0.001), with significant discrimination across all severity pairings. Conclusion: Admission hyperglycemia serves as a superior, graded biomarker for stratifying TBI severity compared to leukocytosis, which functions primarily as a binary threshold marker. The observed immune plateau contrasts with the linear metabolic scaling, highlighting stress-induced hyperglycemia as a critical indicator of severe neuro-metabolic derangement.